Strategi Promosi Program Dokumenter Televisi â€œDoctive: Personaâ€ Melalui Media Sosial Instagram - Pratama, Gustiani Ariani; Oktora, Dina Dwika (Jurnal Ilmiah Multimedia dan Komunikasi, 2024)
One of the success factors of a television program is program promotion. For this reason, a producer has a role to determine the right promotional strategy. The aim of this study is to create a promotional strategy for documentary programs via social media Instagram to attract attention and to provide information about the program being created to the wider public. The creation method used to create promotional content uses the Canva and Adobe Premiere applications which are used to edit video clips and make them into trailers as part of the program's promotional content. The promotional technique used is sharing content about the program through feeds, reels and Instagram stories. Based on the results of the insight review of the Instagram account used as promotional media, it was found that the total number of visits to all uploaded content was 449 visits in one week. The promotion strategy via Instagram social media is successful and it is used appropriately by sharing content in which the features provided by the Instagram can attract the public's attention.